Heritable Changes in Physiological Gas Exchange Traits in Response to Long-Term, Moderate Free-Air Carbon Dioxide Enrichment - Holohan, Aidan David; Müller, Christoph; McElwain, Jennifer (Frontiers in Plant Science, 2019)
Atmospheric carbon dioxide concentrations ([CO2]) significantly alter developmental plant traits with potentially far reaching consequences for ecosystem function and productivity. However, contemporary evolutionary responses amongst extant plant species that coincide with modern, anthropogenically driven [CO2] rise have rarely been demonstrated amongst field grown plant populations. Here we present findings from a long-term, free-air carbon dioxide enrichment (FACE) study in a semi-natural European grassland ecosystem in which we observe a differential capacity amongst plant species to acclimate intrinsic water-use efficiencies (WUEi’s) in response to prolonged, multi-generational exposure to elevated [CO2] concentrations. In a reciprocal swap trial, using controlled environment growth chambers, we germinated seeds from six of the most dominant plant species at the FACE site, (Arrhenatherum elatus (L.), Trisetum flavescens (L.), Holcus lanatus (L.), Geranium pretense (L.), Sanguisorba officinalis (L.), and Plantago lanceolata (L.)). We found that long term exposure to elevated [CO2] strongly influenced the dynamic control of WUEi in the first filial generations (F1) of all species as well as an unequal ability to adapt to changes in the [CO2] of the growth environment amongst those species. Further, despite trait–environment relationships of this nature often being considered evidence for local adaptation in plants we demonstrate that that an ability to increase WUEi does not necessarily translate to an ecological advantage in diverse species mixtures.